PENGARUH STRUKTUR KEPEMILIKAN TERKONSENTRASI DAN KARAKTERISTIK KOMITE AUDIT TERHADAP TINGKAT KEINFORMATIFAN LABA - Muhammad Ibnu Hakim; Fuad Fuad (Diponegoro Journal of Accounting, 2015)
This research aimed to examine the effect of concentrated ownership structure and the audit committee characteristics on the earnings informativeness, as well as examine the negative effect  of  concentrated  ownership  on  the  relationship  of audit  committee  characteristics  with earnings informativeness. Concentrated ownership in this research is based on the percentage shares of ownership in a company. Audit committee characteristics consist of independent, non- financial characteristic, financial expertise, and legal expertise. Control variables in this research are the size of the company, leverage, and market-to-book ratio. This research is based on research conducted by Yeh and Woidtke (2013) and Wawo (2010) with modifications on the variables and sample. This research is modified by making concentrated ownership variable as moderating variable to examine the negative effect of it on the relationship between audit committee characteristics  and  earnings  informativeness.  In  accordance  with  Yeh  and  Woidtke  (2013), earnings informativeness is proxied by relationship between earnings and cumulative abnormal returns (CAR).The research used secondary data from the annual reports of all companies listed on the Indonesian Stock Exchange (IDX) from 2010 to 2013. Sampling method used in this research was purposive sampling. A total sample of 164 companies data were used in analysis. The data is analyzed using multiple linear regression analysis.The  results  of  this  research  indicate  that  concentrated  ownership  negatively  affects earnings  informativeness  and  independence  of  audit  committees  positively  affects  earnings informativeness.   Concentrated   ownership   may   reduce   the   positive   relationship   between independence of the audit committee and earnings informativeness. Nevertheless, the results of this research found no effect of the characteristics of non-financial characteristic, financial expertise, legal expertise on the earnings informativeness. Concentrated ownership does not moderate the relationship of these three characteristics with earnings informativeness.